Static and dynamic properties of a perforated metallic auxetic metamaterial with tunable stiffness and energy absorption - Zhang, Yi; Ren, Xin; Han, Dong; Cheng, Xian; Jiang, Wei; Zhang, Xue Gang; Zhang, Xiang Yu; Xie, Yi Min (International journal of impact engineering, 2022)
•Auxetic metallic metamaterial is designed by variable stiffness factor (VSF) method.•The variable energy factor (VEF) method is proposed.•The accuracies of actual VSF and VEF are discussed under different loading speed.•Layered gradient design can improve mechanical properties of the metamaterials. Auxetic metamaterials have attracted increasing attention due to their exceptional mechanical properties. However, the critical parameters of mechanical response and Poisson's ratio would be changed simultaneously when a geometrical parameter is tuned, which is adverse to achieving the quantitative design of energy absorption by tuning a single geometrical parameter. Thus, the methodology based on tuning densification strain is proposed to design auxetic unit cells with tunable stiffness. In this study, the static performance of 2D metallic auxetic metamaterials designed by the variable stiffness factor (VSF) method is examined experimentally and numerically. To further achieve tunable energy absorption under crushing load, the concept of VSF is extended to variable energy factor (VEF). The dynamic response of verified numerical models is investigated subjected to low-, medium-, and high-velocity crushing. Finally, a functionally graded auxetic structure with different design layers is proposed to effectively solve the issues of high stiffness ratio and initial peak force. These results show that the designed structure has the actual VSF and VEF percentages close to the designed value under low- and medium-velocity crushing. The findings from this study are useful for wider applications of auxetics in protective engineering.